Risk Analysis of Exposure to Particulate Matter (PM10) for Quarry C Mining Workers at PT. X Palu - Ririn Dianatha; Misbahul Subhi; Septia Dwi Cahyani (Universitas Muhammadiyah Palu, 2026)
One of the air pollutants that can cause health problems is particulate matter. Continuous exposure to PM10 can lead to various health issues, especially the ones related to the respiratory system. Workers at PT. X Palu have a higher risk of developing diseases caused by PM10 exposure. This is because they work and remain in an environment with PM10 exposure throughout their working hours. The purpose of this research is to analyze health risks due to PM10 exposure among C mining workers at PT. X Palu. This study used a quantitative descriptive method with an environmental health risk analysis (EHRA) approach. The study population consisted of 15 workers selected using a total sampling technique. PM10 samples were collected using an air sampler. Measurements were taken at 3 location points every hour during operational hours in the mining area, along with filling out observation sheets and interviewing respondents. The results showed that the PM10 concentration outdoor was 0.07777778 mg/m³. This value exceeds the quality standard set by the Ministry of Health Regulation No. 2 of 2023 for a 24-hour period, which is 75 µg/m³ or 0.075 mg/m³. The PM10 intake values ranged from a minimum of 0.0309 mg/kg/day to a maximum of 0.2534 mg/kg/day. The RQ values were ?1, indicating that the workers were not at risk. Based on all the measurements conducted, it can be concluded that although the PM10 concentration at PT. X Palu exceeds the quality standard, the workers are not at risk. It is recommended that PT. X Palu implement health promotion programs for employees to help prevent the health impacts of PM10 exposure, monitor policies regarding the use of personal protective equipment (PPE), and conduct routine medical check-ups for workers.